Programming In C. - Mittal, Ajay. (2010)
This book on C Programming has a perfect blend of theory as well as practicals. The presentation is in such a way that helps the readers to learn the concepts through practice and programming.
10.4.3 Character Input -- 10.4.4 Character Output -- 10.4.5 File Position Indicator -- 10.4.6 End of File and Errors -- 10.4.7 Line Input -- 10.4.8 Line Output -- 10.4.9 Formatted Input -- 10.4.10 Formatted Output -- 10.4.11 Block Input -- 10.4.12 Block Output -- 10.4.13 Stream Buffering and Flushing the Streams -- 10.5 File Type -- 10.6 Files and Command Line Arguments -- 10.7 Summary -- Exercise Questions -- Conceptual Questions and Answers -- Code Snippets -- Multiple-choice Questions -- Outputs and Explanations to Code Snippets -- Answers to Multiple-choice Questions -- Programming Exercises -- Test Yourself -- Appendix A: Number Systems -- A.1 Number systems -- A.2 Number System Conversions -- A.2.1 Conversion from Decimal Number System to any Other Number System -- A.2.2 Conversion from Any Other Number System to Decimal Number System -- A.2.3 Conversion from Binary Number System to Octal and Hexadecimal Number System -- A.2.4 Conversion from Octal and Hexadecimal Number System to Binary Number System -- Appendix B: Algorithms and Flowcharts -- B.1 Algorithm -- B.2 Flowcharts -- Appendix C: Translation Limits -- Appendix D: ROM-BIOS and DOS Services -- Appendix E: Graphics Programming -- E.1 Computer Graphics -- E.2 Initializing Graphics Mode in Turbo C 3.0 -- E.3 Drawing Basic Shapes -- E.3.1 Simple Line Drawing -- E.3.2 Stylish Line Drawing -- E.3.3 Drawing Other Basic Shapes -- E.4 Region Filling -- E.4.1 Filling Regions with Different Patterns and Colors -- E.5 Pattern Drawing Based on Regular Polygons -- E.5.1 Drawing Rosettes -- E.5.2 Swirling Polygons -- E.6 Motif and Tiling -- E.7 Viewport and Clipping -- Appendix F: Answers to Test Yourself Questions -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books